Puzzles tridimensionales con la temática de la Mama Negra, para los niños que padecen TEA, caso de estudio Unidad Educativa Especializada Cotopaxi. - Guanotasig Imbaquingo, Valeria Magaly (2023)
The absence of didactic material in institutions that provide inclusive education to children with special needs has been considered one of the main challenges for children with autism, because this instrument facilitates teaching-learning, as well as acquiring skills for their future. The objective of this research is to create 3D puzzles inspired by the characters of the Mama Negra party to improve the development of cognitive skills in children with autism between 4 and 8 years of age from the Cotopaxi Specialized Educational Unit. The research was carried out in order to gather all the scientific information that helps to corroborate the creation of 3D puzzles. The method used was a qualitative approach through field research, which allowed the collection of information, through the semi-structured interview, empathy map, Focus Group and participant observation directed to the personnel who daily live with the children.